Treatment of acute portomesenteric venous thrombosis with thrombectomy through a transjugular intrahepatic portosystemic shunt: a single-center experience. (August 2018) - Rosenqvist, Kerstin; Ebeling Barbier, Charlotte; Rorsman, Fredrik; Sangfelt, Per; Nyman, Rickard
Background: Acute portomesenteric venous thrombosis (PMVT) is a potentially life-threatening condition and urgent treatment is required. Purpose: To retrospectively evaluate the efficacy and safety of treating acute PMVT by the creation of a transjugular intrahepatic portosystemic shunt (TIPS) followed by thrombectomy. Material and Methods: Six patients (all men, age range = 39–51 years) presenting with acute PMVT were treated with transjugular thrombectomy (TT) through a TIPS created in the same session. The intervention included iterated venography through the TIPS one to three times within the first week after diagnosis and repeated thrombectomy if needed (n = 5). Results: Recanalization was successful with persistent blood flow through the main superior mesenteric vein, portal vein, and TIPS in all six patients. Five patients were treated primarily with thrombectomy through a TIPS with clinical improvement. The final patient was initially treated with surgical thrombectomy and bowel resection. TIPS and TT was performed two days after surgery due to re-thrombosis but the patient deteriorated and died of multi-organ failure. Procedure-related complications were transient hematuria (n = 3) and transient encephalopathy (n = 2). In-hospital time was <14 days in four of the five patients with primary TIPS and TT. No sign of re-thrombosis was noted during follow-up (mean = 18 months, range = 8–28 months). Conclusion: Thrombectomy through a TIPS is feasible and can be effective in recanalization and symptom-relief in acute PMVT.